Constitutive and Synaptic Activation of GIRK Channels Differentiates Mature and Newborn Dentate Granule Cells - Gonzalez, Jose Carlos (J Neurosci, 2018)
Sparse neural activity in the dentate gyrus is enforced by powerful networks of inhibitory GABAergic interneurons in combination with low intrinsic excitability of the principal neurons, the dentate granule cells (GCs). Although the cellular and circuit properties that dictate synaptic inhibition are well studied, less is known about mechanisms that confer low GC intrinsic excitability. Here we demonstrate that intact G protein-mediated signaling contributes to the characteristic low resting membrane potential that differentiates mature dentate GCs from CA1 pyramidal cells and developing adult-born GCs. In mature GCs from male and female mice, intact G protein signaling robustly reduces intrinsic excitability, whereas deletion of G protein-activated inwardly rectifying potassium channel 2 (GIRK2) increases excitability and blocks the effects of G protein signaling on intrinsic properties. Similarly, pharmacological manipulation of GABA(B) receptors (GABA(B)Rs) or GIRK channels alters intrinsic excitability and GC spiking behavior. However, adult-born new GCs lack functional GIRK activity, with phasic and constitutive GABA(B)R-mediated GIRK signaling appearing after several weeks of maturation. Phasic activation is interneuron specific, arising primarily from nNOS-expressing interneurons rather than parvalbumin- or somatostatin-expressing interneurons. Together, these results demonstrate that G protein signaling contributes to the intrinsic excitability that differentiates mature and developing dentate GCs and further suggest that late maturation of GIRK channel activity is poised to convert early developmental functions of GABA(B) receptor signaling into GABA(B)R-mediated inhibition. SIGNIFICANCE STATEMENT The dentate gyrus exhibits sparse neural activity that is essential for the computational function of pattern separation. Sparse activity is ascribed to strong local inhibitory circuits in combination with low intrinsic excitability of the principal neurons, the granule cells. Here we show that constitutive activity of G protein-coupled inwardly rectifying potassium channels (GIRKs) underlies to the hallmark low resting membrane potential and input resistance of mature dentate neurons. Adult-born neurons initially lack functional GIRK channels, with constitutive and phasic GABA(B) receptor-mediated GIRK inhibition developing in tandem after several weeks of maturation. Our results reveal that GABA(B)/GIRK activity is an important determinant of low excitability of mature dentate granule cells that may contribute to sparse DG activity in vivo.